Analisis Kualitatif dan Kuantitatif Metabolit Sekunder Ekstrak Biji Kelor (Moringa oleifera Lam.) dengan Metode Spektrofotometri UV-Vis: Qualitative and Quantitative Analysis of Secondary Metabolite of Moringa Seed Extract (Moringa oleifera Lam.) with UV-Vis Spectrophotometry Method - Tien Wahyu Handayani; Yulistien Yusuf; Joni Tandi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
This study aims to determine the content and total levels of secondary metabolites of ethanol extract of moringa seed (Moringa oleifera Lam.). Extraction of moringa seed using the maceration method to obtain a filtrate. The filtrate obtained was concentrated using a rotary evaporator to obtain a concentrated extract. The extract was tested qualitatively for alkaloids, flavonoids, saponins, and tannins using a suitable reagent with the test parameters. The quantitative test was using UV-Visible spectrophotometry. Alkaloids using test parameters equivalent total alkaloid quinine, flavonoids use parameter test equivalent of the total flavonoids quercetin, saponin using test parameters from Quillaja total saponins and tannins quantitative bark using test parameters total tannin tannic acid equivalent. The result showed that moringa seed positive for alkaloids characterized by orange deposition, flavonoids are characterized by the formation of the yellow color orange, saponin their stable foam, and tannins are marked in black. Quantitative test results alkaloids of 916,87 µg/g, flavonoids of 0.255%, saponin of 6.367%, and tannin of 3,724.5 µg/g. Keywords: Moringa oleifera Lam., secondary metabolites, spectrophotometry